Signs of Statehood of Hamas, Hezbollah and ISIS: Historiographical Review - V. M. Morozov (Научный диалог)
The article is a historiographical study devoted to the analysis of the signs of statehood of such actors of the Middle East policy as Hamas, Hezbollah and ISIS. The purpose of the work is to study the array of scientific literature and on the basis of the extracted data to conclude about the possession of the above actors signs of outcast states, “failed states” and quasi-state entities. Particular attention is paid to the research of individual cases (historical development and the current situation of Hamas, Hezbollah and ISIS), as well as to the works focused on the comparison of these actors. Modern authoritative scientific works on this subject, most of which relate to 2015-2019, were chosen as the basis of the study. The relevance of the study of the characteristics of these organizations is due to the need to expand knowledge about these terrorist groups, understanding of the processes taking place in the unstable Middle East region. On the basis of the literature studied, the author concludes that Hamas, Hezbollah and ISIS have features of both outcast states and “failed states” and quasi-state entities. The author also notes that due to the ongoing wars in the Middle East, the scientific interest in the study of quasi-state Middle Eastern actors in the historiographical sphere will only grow.